Pemanfaatan Air Limbah Kegiatan Domestik Pada Industri Alas Kaki di Kota Madiun Untuk Penyiraman Ruang Terbuka Hijau - Mohammad Najmi Rafi Hakim; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The footwear industry in Madiun City is a planned industry. This industry produces domestic wastewater from domestic activities such as employee and guest toilets, canteens, mosques and building cleaning. The domestic wastewater generated is 97,165 m3/day and will be treated by a WWTP with a capacity of 100 m3/day. The technology used in the WWTP is aerobic biofilter and anaerobic biofilter, which is planned to be able to remove BOD, COD, TSS and ammonia. The results of wastewater treatment by the WWTP have met the quality standards in accordance with the Ministry of Environment and Forestry Regulation No. 68 of 2016 concerning domestic wastewater quality standards. The required irrigation dose for a land area of 38,102.8 m2 is 0.002 m3/m2. Domestic wastewater from the footwear industry in Madiun City as a whole is used to irrigate the Green Open Space and the frequency of irrigation is 2 times in the dry season and 1 time in the rainy season.